Exploring the Views of Secondary School Teachers in Greece on Interactive Educational Tools - Alexandropoulos, Georgios (RADINKA JAYA UTAMA PUBLISHER, 2025)
Teachers' opinions on the use of interactive tools are divided. The purpose of this research is to find out what teachers think about the use of interactive technological tools in the learning process. Despite the potential benefits, there is still a long way to go in understanding the problems teachers face in the classroom. The research that was conducted aims to understand the obstacles, the challenges, and the general assessment of the attitude of educators. By analyzing these tools that will be built in the future, they will be even more efficient, contributing decisively to the change in the learning process. In addition, an e-solution will be proposed by creating interactive material on political poetry. Both the analysis and the research through questionnaires and interviews will pave the way for future research, extensive in sample and scope, and experimental application of interactive material in schools to improve the educational process and achieve the best possible learning outcomes.